Standardising Curriculum Development in the Higher Education Institutions using Higher Education Commission - Issa-Salwe, Abdisalam M.; Maah, Said Ahmed Ali (Advances in Social Sciences Research Journal, 2022)
Because of the lack of a body which can control higher education or make standards that can be shared, the majority of higher education institutions in the Somali Federal Republic fail to have structured and clearly defined curriculum plans. Moreover, some do not even realise the importance of curriculum for their institutions, let alone having clearly defined objectives or goals for educational institutions to achieve in educating society. A curriculum is a map which guides the institution regarding its educational objectives. It is an assessment of how an educational institution defines those objectives. It is also the methods and means through which an educational institution maps out a way for students to find their way to success as defined by those objectives. An institution that plays the role to create a standardised curriculum in higher education is the national higher education commission (HEC). An HEC can stand as a body which regulates higher education, post-secondary education institutions, universities and other public and private higher education institutions. This paper will focus on the importance of curriculum development using examples where HEC can control and set standards which higher education institutions must follow. The paper will particularly try to answer the following questions: (i) How HECs can prescribe guidelines and conditions under which educational institutions set quality curricula, (ii) How HECs can monitor and evaluate the performance of educational institutions, and (iii) How HECs can advise institutions to develop appropriate curricula which balance teaching and learning.